2013
DOI: 10.1007/s11698-013-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

The demand for tobacco in post-unification Italy

Abstract: This paper studies the demand for tobacco products in post-unification Italy. We construct a very detailed panel dataset of yearly consumption in the 69 Italian provinces from 1871 to 1913, and use it to estimate the demand for tobacco products. We find support for the Becker and Murphy (1988) rational addiction model. The empirical analysis further suggests that, in the period considered, tobacco was a normal good in Italy: its consumption increased with income. Subsequently, we consider separately the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Seventeen studies reported price elasticity estimates for smokeless tobacco, of which 13 were from high-income countries (Italy, Sweden and USA). The median own-price elasticity was −0.2 (−0.5, 0.0) for quantity consumed, 21–232638–42 −0.3 (−0.6, 0.0) for participation 394346 and −0.1 (−0.2, 0.0) for intensity among users. 3946 The median cross-price elasticity with respect to cigarettes was −0.7 (−0.8, 1.0) for quantity consumed, 21–232638–42 0.1 (−0.8, 1.0) for participation 4346 and −0.4 for intensity among users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies reported price elasticity estimates for smokeless tobacco, of which 13 were from high-income countries (Italy, Sweden and USA). The median own-price elasticity was −0.2 (−0.5, 0.0) for quantity consumed, 21–232638–42 −0.3 (−0.6, 0.0) for participation 394346 and −0.1 (−0.2, 0.0) for intensity among users. 3946 The median cross-price elasticity with respect to cigarettes was −0.7 (−0.8, 1.0) for quantity consumed, 21–232638–42 0.1 (−0.8, 1.0) for participation 4346 and −0.4 for intensity among users.…”
Section: Resultsmentioning
confidence: 99%
“…Price increases for non-cigarette tobacco products should exceed increases in income because several studies have shown that increasing income results in increased non-cigarette tobacco use. 192639 However, a greater number of studies, all from high-income countries, have shown the inverse that increases in income may reduce demand for non-cigarette tobacco products. 343642–45 Further research is required to drive forward these policies, particularly as non-cigarette tobacco products are often overlooked in the tobacco research and policy discourse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while some studies found that the demand for smokeless tobacco may be as responsive to price as cigarettes,(Chaloupka et al, 1997; Da Pra and Arnade, 2009; Dave and Saffer, 2013; Nguyen et al, 2012; Oshfeldt and Boyle, 1994; Zheng et al, 2017, 2016) other studies indicated that their price elasticities were smaller than that of cigarettes. (Bask and Melkersson, 2003; Ciccarelli and Fraja, 2014; Cotti et al, 2016; Kostova and Dave, 2015; Ohsfeldt et al, 1998, 1997; Tauras et al, 2007) For cigars and little cigars, several studies found very different price elasticity estimates, ranging from −0.05 to −3.17. (Da Pra and Arnade, 2009; Zheng et al, 2017, 2016; Ciccarelli and Fraja, 2014; Gammon et al, 2015; Ringel et al, 2005; Escario and Molina, 2004; Lee et al, 2005; Pekurinen, 1989) Similar mixed results were found for RYO tobacco and loose leaf tobacco as well, with estimates ranging from −0.04 to −0.91.…”
Section: Introductionmentioning
confidence: 99%
“…(Bask and Melkersson, 2003; Ciccarelli and Fraja, 2014; Cotti et al, 2016; Kostova and Dave, 2015; Ohsfeldt et al, 1998, 1997; Tauras et al, 2007) For cigars and little cigars, several studies found very different price elasticity estimates, ranging from −0.05 to −3.17. (Da Pra and Arnade, 2009; Zheng et al, 2017, 2016; Ciccarelli and Fraja, 2014; Gammon et al, 2015; Ringel et al, 2005; Escario and Molina, 2004; Lee et al, 2005; Pekurinen, 1989) Similar mixed results were found for RYO tobacco and loose leaf tobacco as well, with estimates ranging from −0.04 to −0.91. (Cornelsen and Normand, 2014; Da Pra and Arnade, 2009; Mindell and Whynes, 2000; Tait et al, 2015; White and Ross, 2015) Studies that examined the price elasticity of e-cigarettes found that the demand of e-cigarettes, particularly disposable e-cigarettes, was generally price sensitive, with estimated price elasticity in the range of −0.78 to −2.1.…”
Section: Introductionmentioning
confidence: 99%
“…Ciccarelli (2012) describes the relevant historical sources and provides statistical reconstructions of annual regional tobacco consumption in both physical and monetary terms from 1871 to 1913. Ciccarelli and De Fraja (2014) estimate the demand for tobacco in post-unification Italy using annual data at the provincial level, while Ciccarelli and Elhorst (2017) estimate a spatial dynamic panel data model of early cigarettes diffusion in Italy.…”
Section: Literature Reviewmentioning
confidence: 99%